Reduced connexin 43 in eutopic endometrium and cultured endometrial stromal cells from subjects with endometriosis - Yu, Jie; Boicea, Anisoara; Barrett, Kara L; James, Christopher O; Bagchi, Indrani C; Bagchi, Milan K; Nezhat, Ceana; Sidell, Neil; Taylor, Robert N (Molecular human reproduction, 2014)
Accumulating evidence indicates that reduced fecundity associated with endometriosis reflects a failure of embryonic receptivity. Microdomains composed of endometrial gap junctions, which facilitate cell-cell communication, may be implicated. Pharmacological or genetic inhibition of connexin (Cx) 43 block human endometrial cell differentiation in vitro and conditional uterine deletion of Cx43 alleles cause implantation failure in mice. The aim of this study was to determine whether women with endometriosis have reduced eutopic endometrial Cx43. Cx26 acted as a control. Endometrial biopsies were collected from age, race and cycle phase-matched women without (15 controls) or with histologically confirmed endometriosis (15 cases). Immunohistochemistry confirmed a predominant localization of Cx43 in the endometrial stroma, whereas Cx26 was confined to the epithelium. Cx43 immunostaining was reduced in eutopic biopsies of endometriosis subjects and western blotting of tissue lysates confirmed lower Cx43 levels in endometriosis cases, with Cx43/β-actin ratios=.4±1.5 in control and =1.2±0.3 in endometriosis biopsies (P<0.01). When endometrial stromal cells (ESC) were isolated from endometriosis cases, Cx43 levels and scrape loading-dye transfer were reduced by ∼45% compared with ESC from controls. In vitro decidualization of ESC derived from endometriosis versus control subjects resulted in lesser epithelioid transformation and a significantly reduced up-regulation of Cx43 protein (1.2±0.2- versus 1.7±0.4-fold, P<0.01). No changes in Cx26 were observed. While basal steady-state levels of Cx43 mRNA did not differ with respect to controls, ESC from endometriosis cases failed to manifest a response to hormone treatment in vitro. In summary, eutopic endometrial Cx43 concentrations in endometriosis cases were <50% those of controls in vivo and in vitro, functional gap junctions were reduced and hormone-induced Cx43 mRNA levels were blunted.